2018
DOI: 10.1177/1756284818775058
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an optimized colonoscopic screening program for patients with Lynch syndrome: 6-year results of a specialized French network

Abstract: Background:Despite colonoscopic screening, colorectal cancer (CRC) remains frequent in patients with Lynch syndrome (LS). The objective of this study was to evaluate the impact of an optimized colorectal screening program within a French dedicated network.Methods:All LS patients followed at our institution were consecutively included in the Prédisposition au Cancer Colorectal-Ile de France (PRED-IdF) network. Patients were offered an optimized screening program allowing an adjustment of the interval between co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 29 publications
(57 reference statements)
0
19
1
Order By: Relevance
“…Geography and differences in follow-up practices might impact cancer risks, although no significant differences were identified in the most recently updated series of the PLSD study, which included 6350 path_MMR carriers who were prospectively observed for 51,646 follow-up years [4]. A recent single centre and retrospective French study suggested that an optimized colonoscopic surveillance program in LS patients might improve screening quality and possibly decrease CRC occurrence, but long-term prospective studies are needed to confirm these findings [5].…”
Section: Introductionmentioning
confidence: 99%
“…Geography and differences in follow-up practices might impact cancer risks, although no significant differences were identified in the most recently updated series of the PLSD study, which included 6350 path_MMR carriers who were prospectively observed for 51,646 follow-up years [4]. A recent single centre and retrospective French study suggested that an optimized colonoscopic surveillance program in LS patients might improve screening quality and possibly decrease CRC occurrence, but long-term prospective studies are needed to confirm these findings [5].…”
Section: Introductionmentioning
confidence: 99%
“…Adherence to recommended surveillance in Lynch syndrome has been described in 41%–68% of individuals . We found that 57% of the time at risk was spent within recommended surveillance intervals for individuals at risk of first colorectal cancer.…”
Section: Discussionmentioning
confidence: 79%
“…In fact, ADR has been shown to inversely correlate with the risk of incident cancer. 75 Another randomized controlled study analyzing neoplasia detection rates in LS at baseline and follow-up colonoscopy did not find a significant added value for chromoendoscopy over high-definition…”
Section: Performance Of Colonoscopy For Crc Prevention In the Genermentioning
confidence: 96%